2022
DOI: 10.1001/jamahealthforum.2022.0900
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Federal Policy Changes to the Hospice Benefit and Use of Hospice for Persons With ADRD

Abstract: Key Points Question Did hospice use for persons with Alzheimer disease and related dementias (ADRD) change between 2008 and 2019 in conjunction with Medicare policy changes that aimed to reduce long hospice stays? Findings In this cross-sectional study of Medicare claims data from 11 124 992 unique hospice episodes, there were immediate declines in the share of patients receiving hospice care with ADRD and a slower growth in use of hospice care among patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In 2016, CMS increased the routine home care per diem payment for the first 60 days and last 7 days (for decedents) of an episode and lowered the payment for the intervening period. A timeseries study (Gianattasio, Ali, Lupu, Prather, & Power, 2022) found that, after 2014, the proportion of patients admitted with an ADRD diagnosis initially declined but then increased, suggesting that hospices may have initially overestimated the stringency or intensity of audits.…”
Section: Related Literaturementioning
confidence: 99%
“…In 2016, CMS increased the routine home care per diem payment for the first 60 days and last 7 days (for decedents) of an episode and lowered the payment for the intervening period. A timeseries study (Gianattasio, Ali, Lupu, Prather, & Power, 2022) found that, after 2014, the proportion of patients admitted with an ADRD diagnosis initially declined but then increased, suggesting that hospices may have initially overestimated the stringency or intensity of audits.…”
Section: Related Literaturementioning
confidence: 99%